Sharbazher (Shehr-i Bazar) in the Ottoman Archives (1851-1914) - أحمد بژار عثمان; مارف واژەیی دڵشاد عەزیز (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
The historical Sharbazher district covers a vast area including all the valleys, narrow plains and roughed mountains east of Sulaimani, the district called Sharbazher was the capital of Baban Kingdome until building the city of Sulaimani in 1784 AD. After the Ottomans sealed the fate of the Baban princedom in 1851 AD., the Ottomans divided the territories that was under the Babani princedom to numbers of administrative districts, among them Sharbazher (Shehr-i Bazar) district, and it was called a qaza under the Suleymaniye sanjaq in the Mosul Vilayet. After the fall of the Babani Princedom to the fall of the Ottomans Sharbazher district was mentioned in several documents, they are not studied yet, the aim of this paper is studying this important achieve and analyze the political, administrative, social and economic details that was mentioned in these archives. The research methodology of this study uses qualitative historical and textual analysis methods with an exploratory qualitative research design, depending on both primary and secondary sources.